CLIMATE CHANGE AND BIODIVERSITY LOSS: A CRITICAL ANALYSIS OF THE TRIPLE PLANETARY CRISIS - Bansal, Richa (International Journal of Research -GRANTHAALAYAH, 2026)
Climate change and biodiversity loss constitute two interdependent dimensions of the contemporary environmental emergency, increasingly conceptualized within the framework of the “triple planetary crisis,” alongside pollution. This paper critically examines the reciprocal relationship between climate change and biodiversity loss, emphasizing their cumulative impacts on ecosystem stability, human well-being, and sustainable development. Drawing on recent peer-reviewed literature and global environmental assessment reports, the study synthesizes evidence on how climate-induced stressors—such as rising temperatures, altered precipitation patterns, and extreme climatic events—accelerate biodiversity decline across terrestrial and aquatic ecosystems². Conversely, biodiversity degradation weakens ecosystem resilience and undermines natural climate regulation mechanisms, including carbon sequestration³. Using a qualitative integrative methodology, the paper argues that fragmented governance structures limit effective responses to interconnected planetary crises. The study concludes that integrated, ecosystem-based strategies are essential for addressing climate change and biodiversity loss simultaneously.